2020
DOI: 10.1177/1177932220906434
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Arrangement of Pentatricopeptide Domains and the Linker Sequences Between Them

Abstract: The tricopeptide (amino acid number in the 30s) repeats constitute some of the most common amino acid repeats in proteins of diverse organisms. The most important representatives of this class are the 34-residue and 35-residue repeats, eponymously known as tetratricopeptide repeat (TPR) and pentatricopeptide repeat (PPR), respectively. The unit motif of both consists of a pair of alpha helices. As members of the large, all-helical repeat classes, TPR and PPR share structural similarities, but also play specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 81 publications
(81 reference statements)
2
27
0
Order By: Relevance
“…Since the overall interaction energy survey did not show a clearly distinctive profile for Trp, it was inquired if perhaps the location of Trp in proteins exhibits a conspicuous signature. To this end, a previously collected large set of 22,999 pentatricopeptide (35 amino acid) repeats (PPRs) [ 77 ] was analyzed. The PPR is a class of nonidentical 35-amino acid-long repeats that contain signature amino acids in specific positions, and consist of repeat bihelical structures connected by flexible loops [ 77 , 78 , 79 ].…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
See 2 more Smart Citations
“…Since the overall interaction energy survey did not show a clearly distinctive profile for Trp, it was inquired if perhaps the location of Trp in proteins exhibits a conspicuous signature. To this end, a previously collected large set of 22,999 pentatricopeptide (35 amino acid) repeats (PPRs) [ 77 ] was analyzed. The PPR is a class of nonidentical 35-amino acid-long repeats that contain signature amino acids in specific positions, and consist of repeat bihelical structures connected by flexible loops [ 77 , 78 , 79 ].…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
“…To this end, a previously collected large set of 22,999 pentatricopeptide (35 amino acid) repeats (PPRs) [ 77 ] was analyzed. The PPR is a class of nonidentical 35-amino acid-long repeats that contain signature amino acids in specific positions, and consist of repeat bihelical structures connected by flexible loops [ 77 , 78 , 79 ]. In previous studies, the Trp residues in the PPR were shown to be concentrated at residue numbers 3 and 16 [ 77 ].…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
See 1 more Smart Citation
“…To test if the helix-terminal location of Trp is unique to thermophilic proteins, I analyzed the helices in a large number of helix-rich domains, namely the tetratricopeptide repeat (TPR) and the pentatricopeptide repeat (PPR) [ 101 , 102 , 103 , 104 ]. TPR and PPR are, respectively, 34- and 35-amino acid bi-helical motifs, found in diverse proteins that overwhelmingly belong to mesophiles [ 105 , 106 , 107 ].…”
Section: Role Of Specific Amino Acid Residues and Interactionsmentioning
confidence: 99%
“… Near-terminal location of tryptophan (Trp) in all helical repeats. The published collections of the tetratricopeptide and pentatricopeptide repeat sequences [ 102 , 103 ] were visually analyzed for the location of Trp residues, and the numbers were plotted, using Excel. The two classic helices of the tetratricopeptide repeat (TPR) ( Top ) and pentatricopeptide repeat (PPR) ( Bottom ) motif are shown as Helix A and Helix B, and their amino acid position numbers are presented on the horizontal axis.…”
Section: Figurementioning
confidence: 99%